Garanzie o promesse? Le politiche attive per il lavoro nelle Marche dal punto di vista dei beneficiari - Sergi, Vittorio; Giannelli, Nicola; Cefalo, Ruggero (Cambio. Rivista sulle Trasformazioni Sociali, 2017)
In the Marche region Youth Guarantee (YG) registered high levels of adhesion by young people as the subscription rate has reached almost 100% of the estimated target base. The Marche regional government has preferred not to rise high expectations in a large number of young people, offering only those policy measures that was able to fund. Those who seem to have benefited the most of those policies are young people who were already active in seeking a job and who had more expertise or network resources. These don’t attain strictly to the NEET condition. Internships have resulted in real employment when responded to real training projects shared between the worker and the company, otherwise they often risked to become a way to exploit workers at expenses of public budget. Beneficiaries showed a good opinion of training courses but complained about job offers and skills matching on the local market. Weakness and fragmentation of the supply in labour market make difficult a good planning of training needs, especially in the future. Respondents to our interviews can be summarized in three main categories: skilled, confused and disadvantaged. The first ones can benefit from YG limited resources because they have added it to their own social capital; the second ones had troubles in gaining from this chance as they miss some personal or social capital that would fit with plan’s measures; the last ones are not helped and in many cases not even touched by this policy, and unfortunately they are closer to the core of real NEET youth that were expected to be the main target of this active labour market policy.